Preparation method of compact natural color anodic oxide layer of PECVD (Plasma Enhanced Chemical Vapor Deposition) equipment part applied to HJT (High Junction Transistor) type heterojunction cell manufacturing
By adopting the preparation method of a dense natural color anodized layer in the manufacturing of HJT type heterojunction batteries, the problems of uneven porous structure caused by impurities in the electrolytic cell solution and poor film performance are solved, and a denser and corrosion-resistant oxide film is achieved.
Patent Information
- Application Number
- CN202411818669.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
The existing electrolytic cell solution has high content of impurities, resulting in uneven porous structure, poor corrosion resistance and voltage resistance of the membrane layer. In the early stage of the anode, the Barrier layer grows too fast, the membrane layer is not dense, the pore size is large, and the porosity is high, and there are also impurity pollution problems during the sealing process.
The preparation method of a compact natural anodized layer of PECVD equipment parts used in HJT type heterojunction batteries is adopted, including degreasing, alkaline washing, nitric acid polishing, mixed acid polishing, polishing, rinsing and soaking, anodizing, sealing and inspection of workpieces, and the density and uniformity of the oxide film are ensured by controlling the electric field and using ultrapure water.
The problems of dull and light-proof oxide film, uneven porous structure, large porosity, high porosity and impurity pollution during the sealing process were solved, and the denseness, corrosion resistance and voltage resistance of the film layer were significantly improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery oxide layers, and in particular to a method for preparing a dense natural color anode oxide layer of PECVD equipment components used in the manufacture of HJT heterojunction batteries. Background Art
[0002] A battery refers to a cup, trough or other container or part of a composite container that contains an electrolyte solution and a metal electrode to generate an electric current. It is a device that can convert chemical energy into electrical energy. It has a positive electrode and a negative electrode. With the advancement of science and technology, batteries generally refer to small devices that can generate electrical energy. Such as solar cells. The performance parameters of batteries mainly include electromotive force, capacity, specific energy and resistance. Using batteries as an energy source can obtain a current with stable voltage, stable current, long-term stable power supply, and little external influence. In addition, the battery has a simple structure, is easy to carry, and is easy to charge and discharge. It is not affected by external climate and temperature. The performance is stable and reliable, and it plays a great role in all aspects of modern social life.
[0003] However, in actual applications, the existing electrolytic cell solution is sulfuric acid with a concentration controlled at 13-14%. It is industrial grade and has a high content of impurity elements, resulting in an uneven porous structure, poor corrosion resistance and voltage resistance of the film. In addition, the current control method in one stage causes the growth of the barrier layer in the initial stage of the anode to be too fast, the film is not dense, and the pore diameter of the porous structure is about 80nm, which is relatively large. In addition, the sealing method uses boiling water heated from tap water to add nickel salt, and the impurity content of the components after sealing is high, resulting in an uneven porous structure, poor corrosion resistance and voltage resistance of the film. The above three points will lead to certain limitations in the overall operation process, which is not conducive to promotion and use.
[0004] Therefore, those skilled in the art provide a method for preparing a dense natural color anodized layer of a PECVD equipment component used in the manufacture of HJT type heterojunction batteries, in order to solve the problems raised in the above-mentioned background technology. Summary of the invention
[0005] In order to solve the problems proposed in the above background technology that the existing electrolytic cell solution is sulfuric acid with a concentration controlled at 13-14%, and industrial grade is used, the content of impurity elements is relatively high, resulting in uneven porous structure, poor corrosion resistance and voltage resistance of the film layer; and a trial current control method causes the growth process of the barrier layer in the early stage of the anode to be too fast, the film layer is not dense, and the pore diameter of the porous structure is about 80nm, which is relatively large; and the sealing is performed by adding nickel salt to boiling water heated by tap water, and the impurity content of the components after sealing is relatively high, resulting in uneven porous structure, poor corrosion resistance and voltage resistance of the film layer; the above three points will lead to certain limitations in the overall operation process, which is not conducive to the promotion and use of the problem, the present application provides a preparation method of a dense natural color anode oxide layer of PECVD equipment parts used in the manufacture of HJT heterojunction batteries.
[0006] The present application provides a method for preparing a dense natural color anode oxide layer of a PECVD equipment component used in the manufacture of HJT type heterojunction batteries, which adopts the following technical solution: comprising the following steps:
[0007] Step 1: Degreasing and washing after degreasing;
[0008] Step 2: alkali washing, alkali washing and then water washing;
[0009] Step 3: nitric acid polishing and water washing after polishing;
[0010] Step 4: mixed acid polishing;
[0011] Step 5: Polishing and washing after polishing;
[0012] Step 6: Rinse and soak;
[0013] Step 7: anodizing and washing after anodizing;
[0014] Step 8: Sealing holes and removing shielding;
[0015] Step 9: Check the workpiece.
[0016] Preferably, in step 1, the workpiece is immersed in a degreasing solution for degreasing, the degreasing solution comprises soda ash and a surfactant, and after degreasing, the workpiece is immersed in soft water for soaking.
[0017] Preferably, in step 2, the workpiece is immersed in a sodium hydroxide solution, and after alkali washing, the workpiece is immersed in soft water.
[0018] Preferably, in step three, the workpiece is immersed in a nitric acid solution, and after polishing, the workpiece is immersed in soft water.
[0019] Preferably, in step 4, the workpiece is immersed in a 50% sulfuric acid + phosphoric acid solution, and after polishing, the workpiece is immersed in soft water.
[0020] Preferably, in step five, the workpiece is immersed in a 50% ammonium bifluoride solution, and after polishing, the workpiece is immersed in soft water.
[0021] Preferably, in step six, the workpiece is immersed in a rinsing tank for soaking.
[0022] Preferably, in step seven, the workpiece is immersed in 13%-14% sulfuric acid for anodizing. Anodizing is a process in which aluminum is used as the anode and placed in an acid electrolyte solution for electric treatment, and an aluminum oxide film is formed on its surface by electrolysis. After anodizing, an oxide film of several microns or even hundreds of microns can be generated on the aluminum surface, which has significantly improved corrosion resistance, wear resistance and decorative properties compared with natural oxide film. After anodizing, the workpiece is immersed in a rinsing tank for soaking.
[0023] Preferably, in step eight, the workpiece is immersed in the workpiece for sealing, and after sealing, the masking tape and ultra-fine paint on the surface of the workpiece are removed.
[0024] Preferably, in step nine, the appearance of the workpiece is checked visually and the surface of the workpiece is cleaned with a scouring pad, and the film thickness and insulation of the workpiece are checked with measuring tools (thickness gauge, insulation tester).
[0025] In summary, this application includes the following beneficial technical effects:
[0026] 1. Solve the problem of dull oxide film caused by impurities.
[0027] 2. Solve the problem of uneven porous structure, large pore size and high porosity of the anode porous structure due to electric field control problems.
[0028] 3. Solve the sealing ash problem generated during the sealing process and solve the pollution problems of Ca, Zn, K, Na and Mg elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of an electric field control method for preparing a dense natural color anode oxide layer of a PECVD equipment component used in manufacturing an HJT type heterojunction battery in an embodiment of the present application; DETAILED DESCRIPTION
[0030] The described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present application embodiment discloses a method for preparing a dense natural color anode oxide layer of a PECVD equipment component used in the manufacture of an HJT type heterojunction battery, comprising the following steps:
[0032] Step 1: Degreasing and washing after degreasing;
[0033] Step 2: alkali washing, alkali washing and then water washing;
[0034] Step 3: nitric acid polishing and water washing after polishing;
[0035] Step 4: mixed acid polishing;
[0036] Step 5: Polishing and washing after polishing;
[0037] Step 6: Rinse and soak;
[0038] Step 7: anodizing and washing after anodizing;
[0039] Step 8: Sealing holes and removing shielding;
[0040] Step 9: Check the workpiece.
[0041] In the present application, in step 1, the workpiece is immersed in a degreasing preparation liquid for degreasing, the degreasing liquid components are soda ash and a surfactant, and after degreasing, the workpiece is immersed in soft water for soaking.
[0042] In the present application, in step 2, the workpiece is immersed in a sodium hydroxide solution, and after alkali washing, the workpiece is immersed in soft water.
[0043] In the present application, in step three, the workpiece is immersed in a nitric acid solution, and after polishing, the workpiece is immersed in soft water.
[0044] In the present application, in step 4, the workpiece is immersed in a 50% sulfuric acid + phosphoric acid solution, and after polishing, the workpiece is immersed in soft water.
[0045] In the present application, in step five, the workpiece is immersed in a 50% ammonium bifluoride solution, and after polishing, the workpiece is immersed in soft water.
[0046] In the present application, step six is to immerse the workpiece in a rinsing tank.
[0047] In the present application, step seven is to immerse the workpiece in 13%-14% sulfuric acid for anodizing. Anodizing is a process in which aluminum is used as the anode and placed in an acid electrolyte solution for energizing, and an aluminum oxide film is formed on its surface by electrolysis. After anodizing, an oxide film of several microns or even hundreds of microns can be generated on the aluminum surface, which has significantly improved corrosion resistance, wear resistance and decorative properties compared to the natural oxide film. After anodizing, the workpiece is immersed in a rinsing tank for soaking.
[0048] In the present application, step eight is to immerse the workpiece for sealing, and after sealing, remove the masking tape and ultra-fine paint on the surface of the workpiece.
[0049] In the present application, step nine is to visually inspect the appearance of the workpiece and clean the surface of the workpiece with a scouring pad, and use measuring tools (thickness gauge, insulation tester) to inspect the film thickness and insulation of the workpiece.
[0050] The technical creations of the present invention are as follows:
[0051] 1. Anodizing: Immerse the workpiece in 13%-14% stock solution of EL grade sulfuric acid for anodizing, and control the element content below 200PPB.
[0052] S1. Element control index;
[0053] S2. The present invention ensures the uniformity of the electrochemical reaction by controlling the impurity content in the bath solution;
[0054]
[0055]
[0056]
[0057] 2. Control of electric field in anodizing process:
[0058] S1: The present invention adopts a multi-stage electric field control method to ensure the uniformity of the formation of the anode from the BAARIER layer to the porous structure, and the porous structure tends to be dense.
[0059] S2: The electric field is controlled as follows Figure 1 shown.
[0060] 3. Anodizing with ultrapure water for sealing: Immerse the workpiece in ultrapure water with element content controlled below 50ppt for sealing.
[0061] S1: Control the element impurity level in the sealing bath solution as follows:
[0062]
[0063]
[0064]
[0065] In addition, the effect of bath impurities on anodizing is improved:
[0066] Chloride ions, sulfate ions and trivalent chromium ions in the anodizing electrolyte are harmful impurities. Chloride ions can cause etching of parts; an increase in the number of sulfate ions can cause the oxide film to change from transparent to opaque and shorten the service life of the bath; too much trivalent chromium ions can cause the oxide film to become dark and matte; during the anodizing process, under the action of the electric field, the migrating ions are mainly divided into four parts;
[0067] A13+ migrates outwards. Because metal aluminum is face-centered cubic close-packed, it is difficult for the A13+ ions formed at the aluminum matrix interface to migrate out of the unit cell. In the seriously polluted layer or at the interface between the polluted layer and the electrolyte, A1203 dissolves to produce A13+. A13+ may migrate into the solution or react with the anions in the polluted layer to form new compounds.
[0068] A1→A13++3e-; A1203+6H+→2A13++3H20; A13++P033-→A1P03; 0H- (or 02-) ions migrate inwards. Due to their relatively small ionic radius, they are easier to migrate and react with the contacted A13+ ions to form aluminum oxide. In addition, 0- (or 02-) will generate 02 after discharge; 2A13++30H--A1203+3H+; 202--02+4e-; H+ migrates outwards. 0H- reacts with aluminum to generate H+ ions with a very small ionic radius. Under the action of the electric field, H+ moves rapidly and reacts with aluminum oxide at the solution interface to form water and A13+ ions. The A13+ ions enter the solution, which is acidic field-induced dissolution.
[0069] Other anions in the electrolyte migrate into the membrane layer: Since these anions have a large ion radius, it is difficult for them to migrate into the interior of the barrier layer of aluminum oxide. Therefore, they are mainly concentrated in the outer layer close to the electrolyte, forming a contamination layer. The contamination layer causes the membrane structure of the original barrier layer to be destroyed, and the infiltration of the electrolyte causes the resistance to be greatly reduced.
[0070] In addition, the effect of the three-stage electric field on the porous structure of anodized film:
[0071] The present invention draws on the electric field dissolution model of anodization21, which believes that the anodization process of aluminum includes three main stages: the formation of a barrier layer, the dissolution of the barrier layer, and the stable growth of a porous layer.
[0072] When voltage is applied to both ends of the electrode, the resistance in the circuit is very low and the current is very high, forming a solid and dense non-ferrous aluminum oxide film on the anode aluminum film, called a barrier layer. Since the aluminum oxide just generated from the solution is easily soluble in the acid solution, part of the aluminum oxide undergoes chemical dissolution. When the barrier layer reaches a certain critical value, the electrolyte begins to dissolve the initial pore nuclei at the regularly arranged points on the surface of the barrier layer. The formation of the pore nuclei will concentrate the originally uniformly distributed electric field in the bottom area of the pore 146, thereby greatly enhancing the dissolution rate of the barrier layer at the bottom of the pore. At the same time, due to the enhancement of the local electric field at the bottom of the pore and the increase of the current, local overheating is caused, which accelerates the dissolution process. While dissolving, a new barrier layer begins to form at the barrier layer / aluminum film interface. At this time, under the action of the electric field, A" migrates outward, while 0- or OH migrates inward, thereby continuously forming a barrier layer. Finally, the dissolution rate and growth rate of the barrier layer will reach a dynamic equilibrium, entering the stable growth stage of the porous layer.
[0073] In addition, the reaction mechanism of ultrapure water sealing:
[0074] The essence of heat sealing is hydration reaction, often called "hydration-heat sealing" (hytro-themal sealing), which can be written as the following reaction equation: Al203+H20--AI203·H20(A100H);
[0075] The pore size of the sulfuric acid anodized porous membrane is very small, about 15 to 25 nm. During the sealing process, OH diffuses into the pores of the oxide film. As long as the diffusion process is the controlling step of the sealing speed, the change of the sealing speed with time should be a nonlinear relationship. In other words, the sealing degree is not proportional to the sealing time. The speed is faster at the beginning and then gradually decreases;
[0076] The molecular composition of the anode layer after hot pure water sealing is aluminum oxide (80%), aluminum sulfate (18%), and water (2%).
[0077] Secondly: In the drawings of the embodiments disclosed in the present invention, only the structures involved in the embodiments disclosed in the present invention are involved, and other structures can refer to the usual design. In the absence of conflict, the same embodiment and different embodiments of the present invention can be combined with each other.
Claims
1. A method for preparing a dense natural color anodized layer of a PECVD equipment component used in the manufacture of HJT type heterojunction batteries, characterized in that: The steps include: Step 1: Degreasing and washing after degreasing; Step 2: alkali washing, alkali washing and then water washing; Step 3: nitric acid polishing and water washing after polishing; Step 4: mixed acid polishing; Step 5: Polishing and washing after polishing; Step 6: Rinse and soak; Step 7: anodizing and washing after anodizing; Step 8: Sealing holes and removing shielding; Step 9: Check the workpiece.
2. The method for preparing a dense natural color anodized layer of a PECVD equipment component used in the manufacture of a HJT type heterojunction battery according to claim 1, characterized in that: In the step 1, the workpiece is immersed in a degreasing solution for degreasing, the degreasing solution comprises soda ash and a surfactant, and after degreasing, the workpiece is immersed in soft water for soaking.
3. The method for preparing a dense natural color anodized layer of a PECVD equipment component used in the manufacture of a HJT type heterojunction battery according to claim 1, characterized in that: In the step 2, the workpiece is immersed in a sodium hydroxide solution, and after alkali washing, the workpiece is immersed in soft water.
4. The method for preparing a dense natural color anodized layer of a PECVD equipment component used in the manufacture of a HJT type heterojunction battery according to claim 1, characterized in that: In the step three, the workpiece is immersed in a nitric acid solution, and after polishing, the workpiece is immersed in soft water.
5. The method for preparing a dense natural color anodized layer of a PECVD equipment component used in the manufacture of a HJT type heterojunction battery according to claim 1, characterized in that: In the step 4, the workpiece is immersed in a 50% sulfuric acid + phosphoric acid solution, and after polishing, the workpiece is immersed in soft water.
6. The method for preparing a dense natural color anodized layer of a PECVD equipment component used in the manufacture of a HJT type heterojunction battery according to claim 1, characterized in that: In the step 5, the workpiece is immersed in a 50% ammonium bifluoride solution, and after polishing, the workpiece is immersed in soft water.
7. The method for preparing a dense natural color anodized layer of a PECVD equipment component used in the manufacture of a HJT type heterojunction battery according to claim 1, characterized in that: In the step six, the workpiece is immersed in a rinsing tank for soaking.
8. The method for preparing a dense natural color anodized layer of a PECVD equipment component used in the manufacture of a HJT type heterojunction battery according to claim 1, characterized in that: In step seven, the workpiece is immersed in 13%-14% sulfuric acid for anodization. Anodization is a process in which aluminum is used as an anode and placed in an acid electrolyte solution for energization to form an aluminum oxide film on its surface by electrolysis. After anodizing treatment, an oxide film of several microns or even hundreds of microns can be generated on the aluminum surface, which has significantly improved corrosion resistance, wear resistance and decorative properties compared to the natural oxide film. After anodizing, the workpiece is immersed in a rinsing tank.
9. The method for preparing a dense natural color anodized layer of a PECVD equipment component used in the manufacture of a HJT type heterojunction battery according to claim 1, characterized in that: In the step eight, the workpiece is immersed in the workpiece for sealing, and after the sealing, the masking tape and ultra-fine paint on the surface of the workpiece are removed.
10. The method for preparing a dense natural color anodized layer of a PECVD equipment component used in manufacturing a HJT type heterojunction battery according to claim 1, characterized in that: In the step nine, the appearance of the workpiece is checked visually and the surface of the workpiece is cleaned with a scouring pad, and the film thickness and insulation of the workpiece are checked with measuring tools (thickness gauge, insulation tester).